2019
DOI: 10.2147/ott.s227541
|View full text |Cite
|
Sign up to set email alerts
|

<p>MIR22HG As A Tumor Suppressive lncRNA In HCC: A Comprehensive Analysis Integrating RT-qPCR, mRNA-Seq, And Microarrays</p>

Abstract: Introduction: MIR22HG has a reported involvement in the tumorigenesis of a variety of cancers, including hepatocellular carcinoma (HCC). However, the exact molecular mechanism of MIR22HG in HCC has not been clarified. Methods: In the present study, we integrated data from in-house RT-qPCR, RNA-sequencing, microarray, and literature studies to conduct a comprehensive evaluation of the clinicopathological and prognostic significance of MIR22HG in an extremely large group of HCC samples. We also explored the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…As demonstrated previously, a decreased MAOA was detected in HCC patients and correlated with poor prognosis. Our previous studies have confirmed the anti‐HCC effect of NC 34,35,37 . In this study, in vivo experiment showed that the tumor volumes were reduced and the MAOA expression level was significantly elevated in the NC‐treated group compared with the control group.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As demonstrated previously, a decreased MAOA was detected in HCC patients and correlated with poor prognosis. Our previous studies have confirmed the anti‐HCC effect of NC 34,35,37 . In this study, in vivo experiment showed that the tumor volumes were reduced and the MAOA expression level was significantly elevated in the NC‐treated group compared with the control group.…”
Section: Discussionsupporting
confidence: 77%
“…Our team has been studying the biological function NC has on HCC for a period. Previous in vitro and in vivo studies have verified that TCM NC exhibits a strong anti‐HCC capability by mediating complicated mechanisms, namely TF‐miRNA‐mRNA axis, circRNA‐miRNA‐mRNA network, andJAK1/STAT3 cascade signaling inhibition 34‐38 . Given the role that MAOA plays in HCC, we supposed that NC could exert its anti‐tumor effect partially by influencing the expression of MAOA .…”
Section: Methodsmentioning
confidence: 91%
“…We first examined the expression of TRIM21 in human HCC using publicly available datasets. In the Gene Expression Omnibus Series, 19 6 of 18 studies showed elevated TRIM21 expression in HCC comparing with normal liver tissues ( Figure 1 A ). The Cancer Genome Atlas (TCGA) also showed that TRIM21 transcript level is elevated in tumor tissues and positively correlates with disease progression ( Figure 1 B ), and that the expression level of TRIM21 correlates with a worse overall survival although not with disease-free survival ( Figure 1 C ).…”
Section: Resultsmentioning
confidence: 99%
“…LncRNA MIR22HG, which is located on chromosome 17p13.3, has been discovered to play roles in a variety of cancers. Many previous studies revealed that MIR22HG exhibited tumor-suppressive role in several types of cancer including lung cancer, hepatocellular carcinoma, endometrial cancer, gastric cancer and cholangiocarcinoma, and its low expression was associated with poor prognosis [12][13][14][15][16][17] . Conversely, some studies showed that MIR22HG played an oncogenic function in several cancer types such as glioblastoma, and MIR22HG knockdown inhibits the invasion and proliferation of cancer cells 18 .…”
Section: Introductionmentioning
confidence: 99%